Acoustic analysis of vocalization and the behavioral response associated to sound production of the nine banded armadillo Dasypus novemcinctus (Mammalia, Cingulata, Dasypodidae) in an agonistic context - Costa, Fabiana Rodrigues; Moura, Pedro Henrique Areco Gomes [UNESP]; Alves-Júnior, Sérgio da Rocha; Rosa, Patricia Sammarco; Nunes, Ivan [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2022)
Although communication capabilities are displayed by many vertebrate groups, some repertoires are poorly known, such as the case of xenarthrans, particularly armadillos, for which vocalization as a source of communicating to others remains poorly understood and relies on punctual reports of sounds. Here we provide the first description of a behavioral response associated with sound emission of two subjects of Dasypus novemcinctus. Both audio and visual registration was performed to subsequent analyses of expressed behaviors and emitted calls, which accounted for 76 vocalizations from a total of eight video recordings randomly collected from 2017 to 2019. Sound is acoustically characterized by both inhale and exhale phases composed of two vocal units, and no harmonic structure was observed. Once the subjects have always produced these vocalizations while cornered and exhibiting defensive behavior against another subject/human disturbance, these vocalizations were termed as distress. Subjects produced a hiss-purr-like sound while trying to avoid contact with another by bowing or lowering their bodies, humping, or even moving elsewhere when sound production ceased. This shows that the sound repertoire of armadillos is still to be unveiled and seems to be much more complex than previously thought.
Keywords: Behavioral repertoire; Bioacoustics; Cingulates; Ethology; Xenarthra